Peranan guru dalam memupuk kreativiti pelajar - Mohamad Mohsin Mohamad Said,; Nasruddin Yunos, (Universiti Kebangsaan Malaysia, 2008)
The development of creative and innovative human capital is one of the main aspects highlighted in the 9th Malaysian Plan. At one time, creativity is believed to be an inborn quality, inherited by the privileged few. However, lately psychologists believed that everybody has the potential to be creative. In order to stimulate creativity, continued and systematic effort has to be carried out. Creativity can be nurtured and enhanced through education. This paper will discuss the concept of creativity, the implementation of creativity in the Malaysian educational systems and various approaches that can be applied by teachers to enhance creativity among school students